THE APPLICATION OF SLEEP HYGIENE THERAPY IN ELEMENTARY SCHOOL AGE CHILDREN WITH SLEEP DISORDERS PROBLEMS IN SERENGAN VILLAGE - Dwi Lestari Mukti Palupi; Ikrima Rahmasari (LPPM Universitas Duta Bangsa Surakarta, 2022)
Sleep is a repetitive neurobehavioral state of relative perceptual detachment and is not responsive to the environment, accompanied by a reclining position, calm behavior and closed eyes, which are important for health (Buysse, 2014). Sleep quantity disturbance is the non- fulfillment of normal sleep duration, which can result from difficulty initiating sleep or inability to maintain sleep. Sleep quality disorders are sleep interruptions due to awakening when sleep is of short duration but with frequent and repeated frequency (Cortese, et al. 2014). Sleep hygiene therapy is the most effective non-pharmacological therapy to overcome sleep pattern disorders (Yaremchuk, 2018). The general purpose of this case is to provide